RETRACTED: Applying case-based reasoning in social computing to transform colors into music. (June 2018) - Navarro-Cáceres, María; Rodríguez, Sara; Bajo, Javier; Corchado, Juan Manuel
Abstract: This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our-business/policies/article-withdrawal ). This article has been retracted at the request of the authors and the Editor-in-Chief.Since publication of thepaper, the corresponding author has become aware of content duplication with a Master's Thesis published athttps://gredos.usal.es/jspui/handle/10366/137433, related to the software tool used to evaluate the proposal. The authors accept that the section of the article presenting the evaluation process, and more specifically that describing the software tool, contains duplications and, for this reason, they wish to retract the article. Note, however, that the method described in this paper is completely new and has been validated through the results.